2018
DOI: 10.5861/ijrsp.2018.3005
|View full text |Cite
|
Sign up to set email alerts
|

“I’m perfectly imperfect”: Exploring the relationship between PERMA model of wellbeing with self-esteem among persons with disabilities

Abstract: Most of the studies that measure wellbeing using the PERMA Model were from the school context most commonly students and staffs. In the current study, the new model of wellbeing was applied to the Persons with Disabilities (PWD) and look for its relationship to self-esteem.PERMA Profiler was used in measuring wellbeing for the PWDs and Rosenberg Self-Esteem Scale for their self-esteem. For the result, the study found that PWDs have moderately high level of wellbeing despite of their conditions but low level in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“… Butler and Kern (2016) reported that adequate reliability is observed for overall well-being and all subscales, α range from 0.71 to 0.94 across eight studies ( N = 31,966). According to Nebrida and Dullas (2018) , the Tagalog version of the PERMA Profiler has a Cronbach’s alpha of 0.842 in 101 Filipino participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Butler and Kern (2016) reported that adequate reliability is observed for overall well-being and all subscales, α range from 0.71 to 0.94 across eight studies ( N = 31,966). According to Nebrida and Dullas (2018) , the Tagalog version of the PERMA Profiler has a Cronbach’s alpha of 0.842 in 101 Filipino participants.…”
Section: Methodsmentioning
confidence: 99%
“…Seligman (2011) argued that people pursue accomplishments even when they do not result in positive emotions, meaning, or relationships. Although PERMA was developed mainly within the Western context, several researches found that PERMA is experienced in culturally consistent manners in non-Western societies such as the United Arab Emirates ( Lambert and Pasha-Zaidi, 2016 ), Hong-Kong ( Lai et al, 2018 ), and the Philippines ( Nebrida and Dullas, 2018 ).…”
Section: Well-being and Its Elementsmentioning
confidence: 99%
“…On the other hand, Castillo (2017) stated that personality traits could be defined as the way an individual's mental world is set in a world that is stable and consistent over time. When it comes to personality traits, one of the most famous and useful models is the Big five model (McCrae and John, 1992) in diverse cultures like American-English, Czech, Dutch, Flemish, Filipino, German, Hungarian, Italian, Japanese, Romanian, and Russian (de Raad, 2000). The following are the five personality traits that will be defined.…”
Section: Personality Traits and Deviant Behaviormentioning
confidence: 99%
“…Openness to experience is defined as the openness of an individual which is viewed as willingness to look for new experiences and embrace changes, level creativity, and exploration of unfamiliar things (McCrae and John, 1992;Castillo, 2017). Furthermore, individuals with high potential to be open to experiences are considered as willing to experience changes and new adventures in their lives (Jia et al, 2013).…”
Section: Personality Traits and Deviant Behaviormentioning
confidence: 99%
See 1 more Smart Citation